Chorioangioma in pregnancy: a case report - Rio Yoga Erlambang; I Wayan Artana Putra (Intisari Sains Medis, 2021)
Background: Placental chorioangioma is a rare benign non-trophoblastic tumor of the placenta, derived from primitive chorionic mesenchyme. It can cause adverse outcomes on the mother and fetus, depending on its size. Most of the cases are accidentally detected during ultrasonography because small size tumors are usually asymptomatic. However, larger size of tumor can cause complications such as fetal anemia, fetal hydrops, polyhydramnios, premature birth, intrauterine growth restriction, and fetal death.Case report: A 27-year-old primigravida presented at Sanglah Hospital gynecology polyclinic at 27th-28th week of gestation. She was referred by an obstetric and gynecologist due to polyhydramnion since 26th-27th week of gestation. A 7.86 x 8.19 cm hypoechoic cysts with hyperechoic border were found during fetal scanning. Chorioangioma was suspected with SDP 9.11 cm. Amniocentesis was planned, however the patient had a premature uterine contraction. By this time, the fundal height was accordant with 31st-32nd week of gestation, and speculum examination showed rupture of membrane with 4 cm cervix dilation. Spontaneous vaginal delivery was performed and a boy neonate with 4/6 Apgar score and birth weight of 1150 g was delivered. Placenta was extracted out completely. There was no complication after delivery process. Macroscopic and microscopic placental examination confirmed the initial diagnosis, chorioangioma.Conclusion: Early management in determining the cause of polyhydroamnion is challenging and needs comprehensive investigation. Ultrasonography is a choice of method in initial detection of polyhydroamnion. Serial ultrasonography is needed to evaluate the amount of amniotic fluid and detect the probable cause of complications for mother, fetus, and delivery process. One of the complications is premature uterine contraction that causes premature birth. As a result, the fetus may not be viable and this remains one of the biggest challenges for clinicians. There are several possible causes that cannot be ruled out from polyhydroamnion differential diagnoses, such as a rare placental tumor chorioangioma.